STRATEGI KEDISIPLINAN GURU DAN TENAGA ADMINISTRASI DALAM MENINGKATKAN PRESTASI PESERTA DIDIK (Studi pada SMAN 1 Baradatu Kabupaten Way Kanan) - . Sutamto (Universitas Bandar Lampung (UBL), 2016)
An increase in discipline teacher will effect on improving the achievements of learners it is because the teacher's role in the management of teaching components used in the process of teaching and learning. In addition to the support from the teachers administration also strongly affect the achievements of learners it in power administration is claiming it's vital for the effectiveness of the institution. Based on the objectives in this research is to know and explore the strategy discipline teachers and administration personnel in improving the achievements of learners at State Senior High School 1 Regency Way Kanan Baradatu.The design used in this study is a qualitative research design, the techniques used in collecting data, among others, by way of observation, interview and documentation. Data analysis technique used is an interactive model of analysis that includes the reduction of the data, the presentation of data and verification.Based on the results of the study can then note that: (1) implementation of strategy discipline teachers and administration personnel in improving the achievements of learners is by the way teachers and administrative personnel have always included training and seminars, the principal always implement banding study, teachers require to participate in the activities of the administration in power and the subject teacher conference require to always join the managerial training (2) the Supervision is exercised through the principal always do coordination and see firsthand the State of teachers and administrative personnel in both learning activities as well as in implementation of management education (3) creativity of teachers and administrative personnel can be categorized already good enough this can be seen from the everyday life of teachers and administrative personnel who've been fullest use of media in learning and technology in the finalizing of the work keadministrasian (4) educators to develop educational and implementation strategies in optimizing discipline teachers and school administrative personnel then do some way as deliberation of teachers of subjects subject teacher conference , motivating teachers and administrative staff, provide the motivation to teachers to follow, require certification to follow the activities of the workshop as well as intensify the evaluation meeting every week. Key Words: Strategy Discipline, Improve Learner Achievements